Z3Guide: A Scalable, Student-Centered, and Extensible Educational Environment for Logic Modeling - Huang, Ruanqianqian (Lisa); Monroe, Ayana; Halleux, Jonathan "Peli" de; Lerner, Sorin; Bjørner, Nikolaj (Microsoft, 2025)
Constraint-satisfaction problems (CSPs) are ubiquitous, ranging from budgeting for grocery shopping to verifying software behavior. Logic modeling helps solve CSPs programmatically using SMT solvers. Despite its importance in many Computer Science disciplines, resources for teaching and learning logic modeling are scarce and scattered, and challenges remain in designing educational environments for logic modeling that are accessible and meet the needs of teachers and students. This paper explores how to design such an environment and probes the impact of the design on the learning experience. From a need-finding interview study and a design iteration with teachers of logic modeling, we curated 10 design guidelines spanning three main requirements: providing easy access, supporting various educational modalities, and allowing extensions for customized pedagogical needs. We implemented nine guidelines in Z3Guide, an open-source browser-based tool. Using Z3Guide in a logic modeling learning workshop with more than 100 students, we gathered positive feedback on its support for learning and identified opportunities for future improvements.